Literacy Alley: Efforts to Enhance Literacy Passion Among Students at Kanisius Demangan Baru Yogyakarta Elementary School - Nurhayati Nurhayati; Agus Herwanto; Marwan Marwan (Jurnal Indonesia Sosial Sains, 2024)
This study aims to explore and evaluate the efforts made in increasing literacy love in students of Kanisius Demangan Baru Elementary School (SD) in Yogyakarta. Literacy plays a crucial role in students' intellectual and social development, and an understanding and appreciation of literacy can enrich their educational experience. This research method involves collecting qualitative data through classroom observation, interviews with teachers and students, as well as analyzing documents related to literacy programs that have been implemented, and finally drawing conclusions. The results showed that efforts to increase love for literacy involve innovative teaching strategies and integrating literacy into the curriculum. Teachers actively promote students' interest in reading through activities such as book discussion groups, story and storytelling performances, library visits, promoting literacy corner projects in classrooms, and enlivening school walls and hallways with student literacy works. In addition, science literacy programs can also improve students' knowledge of nature, and storytelling teacher programs can improve teachers' and students' abilities with literary appreciation. The evaluation results showed a positive increase in students' reading interest and literacy understanding. The findings may provide insight for other schools looking to increase the love of literacy at the primary level, emphasizing the importance of collaboration between teachers, students, and parents in creating an educational environment that supports children's literacy development.